2020
DOI: 10.1210/clinem/dgaa820
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation In Situ in Breasts at High Risk of Cancer: Relationship with Mammographic Density and Estradiol

Abstract: Context High mammographic density in postmenopausal women is an independent risk factor for breast cancer by undetermined mechanisms. No preventive therapy for this risk group is available. Activated platelets release growth factors that modulate the microenvironment into a pro-tumorigenic state. Estrogens may affect the risk of breast cancer and platelet function. Whether platelets are activated in situ in breast cancer or in normal breast tissue at high risk of breast cancer and the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…42 Lymphocytes influence the growth of tumor cells and improve the prognosis of patients with malignant tumors by secreting interferon-gamma and tumor necrosis factor-α. 43 Platelets protect the circulating tumor cells in the peripheral blood from flow shear stress, induce the epithelial-mesenchymal transition, and promote the tumor cells to extravasate to the metastatic site. 44 Studies have demonstrated that cancer cells overproduce proinflammatory mediators, such as IL-6 and IL-10, and increase the count of neutrophils and platelets in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…42 Lymphocytes influence the growth of tumor cells and improve the prognosis of patients with malignant tumors by secreting interferon-gamma and tumor necrosis factor-α. 43 Platelets protect the circulating tumor cells in the peripheral blood from flow shear stress, induce the epithelial-mesenchymal transition, and promote the tumor cells to extravasate to the metastatic site. 44 Studies have demonstrated that cancer cells overproduce proinflammatory mediators, such as IL-6 and IL-10, and increase the count of neutrophils and platelets in peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…The microdialysis samples were analyzed using a multiplex proximity extension assay (PEA, Olink Bioscience, Uppsala Sweden) as previously described ( 29 31 ). In brief, 1 μL sample was incubated with proximity antibody pairs tagged with DNA reporter molecules.…”
Section: Methodsmentioning
confidence: 99%
“…Thus 91 out of the 92 proteins were quantified circulating in plasma of healthy individuals during the validation of the assay; https://www.olink.com/content/uploads/2021/09/olinkmetabolism-validation-data-v2.0.pdf. In the present study, microdialysis samples were analyzed with multiplex proximity extension assay (PEA, Olink Bioscience, Uppsala Sweden) as previously described (32)(33)(34). In brief, 1 mL microdialysis sample was incubated with proximity antibody pairs tagged with DNA reporter molecules.…”
Section: Protein Quantificationsmentioning
confidence: 99%